Micro-electrical Discharge Machining Processes Technologies and Applications - Kibria, Golam; Jahan, Muhammad P.; Bhattacharyya, B.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book offers a comprehensive collection of micro electrical discharge machining (EDM) processes, including hybrid processes. It discusses the theory behind each process and their applications in various technological as well as biomedical domains, and also presents a brief background to various micro EDM processes, current research challenges, and detailed case studies of micro-manufacturing miniaturized parts. The book serves as a valuable guide for students and researchers interested in micro EDM and other related processes. .
1. Introduction -- 2. Micro EDM drilling -- 3. Micro wire EDM -- 4. Micro EDM milling -- 5. Dry and near-dry micro EDM -- 6. Micro electrical discharge grinding -- 7. Reverse micro EDM -- 8. Powder mixed micro EDM -- 9. Ultrasonic vibration assisted micro EDM -- 10. Laser assisted micro EDM -- 11. Sequential micro EDM -- 12. Piezoelectric self-adaptive micro EDM -- 13. Other hybrid processes using micro EDM.
Keywords: Manufactures; Materials; Machinery; Machines, Tools, Processes; Materials Engineering; Machinery and Machine Elements